Dealing with DOMA: Federal Non-Recognition Complicates State Income Taxation of Same-Sex Relationships - Smith, Carlton; Stein, Edward (Columbia Journal of Gender and Law, 2012)
Various states now recognize relationships between people of the same sex, but due to the Defense of Marriage Act, the federal government does not. In the context of income taxes, this combination of state recognition and federal non-recognition of same-sex relationships produces a significant problem for many same-sex couples and some state taxing authorities. Most states have income tax and, typically, state income tax laws “piggyback” on federal income tax laws. Depending on the state, same-sex couples in legally-recognized relationships must file their state income tax returns as married (either “filing jointly” or “filing separately”), as domestic partners, or as parties to a civil union. Such same-sex couples cannot, however,-file their federal-income tax returns as a couple. For same-sex couples, this situation creates uncertainty and complications and probably increases the risk of audit. It is also an unfair affront to the dignity of lesbians, gay men, and bisexuals. The Article examines this problem by surveying the guidance from thirteen states and the District of Columbia with respect to the taxation of same-sex relationships and by considering each jurisdiction’s actual income tax practices. The Article also recommends best practices for state taxing authorities, including: (1) amending state tax laws to specifically allow joint filing by same-sex couples; (2) issuing more guidance to same-sex couples on specific relevant issues; (3) adding boxes to state tax returns to indicate that these returns will involve nonconformity with federal filing status; and (4) not requiring same-sex couples who file state joint income tax returns to also complete “pro forma” federal “married” income tax returns.